Nutritional status of U.S. elite heptathletes - 2001 USA track and field development project - Houtkooper, L. B.; Mullins, V. A.; Maurer, J.; Taylor, A.; Poole, C. (2001)
This study describes the body composition, dietary nutrient intake, dietary practices, and biochemical indices of iron status of elite female American heptathletes during training. Four-day diet records and dietary practice questionnaires were obtained from 19 female heptathletes (26±3 years) during the training season. Anthropometric measurements and fasting blood samples were obtained at the lowest phase of the training cycle. These athletes had a low body fat (13.8±2.7%) and high fat-free mass to height ratios (33.0±2.0 kg/m). Average nutrient intakes were >67% of the reference intakes for all nutrients except for vitamin E. Most dietary nutrient densities were higher than NHANES III nutrient densities for women 20-29 years old. More than 50% of the athletes took vitamin supplements and monitored their hydration status. Fifteen of the 17 athletes reported a normal menstrual cycle. Markers of biochemical iron status were all within the normal range. On average, these athletes were lean with high levels of fat free mass, adequate nutrient intakes, and normal biochemical indices of iron status. However, individual data reveals considerable variability within this group.